A patent review of adenosine A2B receptor antagonists (2016-present). (3rd June 2022) - Francucci, Beatrice; Dal Ben, Diego; Lambertucci, Catia; Spinaci, Andrea; Volpini, Rosaria; Marucci, Gabriella; Buccioni, Michela
ABSTRACT: Introduction: A2B adenosine receptor (A2B AR) plays a crucial role in pathophysiologic conditions associated with high adenosine release, typical of airway inflammatory pathologies, gastrointestinal disorders, cancer, asthma, type 2 diabetes, and atherosclerosis. In some pathologies, simultaneous inactivation of A2A and A2B ARs is desirable to have a synergism of action that leads to a greater efficacy of the pharmacological treatment and less side effects due to the dose of drug administered. In this context, it is strongly required to identify molecules capable of selectively antagonizing A2B AR or A2A /A2B ARs. Areas covered: The review provides a summary of patents, published from 2016 to present, on chemicals and their clinical use. In this paper, information on the biological activity of representative structures of recently developed A2B or A2A /A2B receptor ligands is reported. Expert opinion: Among the four P1 receptors, A2B AR is the most inscrutable and the least studied until a few years ago, but its involvement in various inflammatory pathologies has recently made it a pharmacological target of high interest. Many efforts by the academy and pharmaceutical companies have been made to discover potential A2B AR and A2A /A2B ARs drugs. Although several compounds have been synthesized only a few molecules have entered clinical trials.